Manajemen Keuangan Pondok Pesantren - ARIFIN, MIFTAHOL (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2016)
There are three factors that has significant role in the organization of Islamicboarding school system. Those are, management as the factor of efforts, theorganization as the factor of Facility, and the administration as the factor ofintention. These three factors give direction and cohesion in defining, controlling,organizing, supervising and assessing the implementation of the policies in aneffort to organize educational activities in accordance with the aim of every Islamicboarding school.One of the components of management in an effort to Islamic boarding schoolis financial management. Financial management of the Islamic boarding school isan activity undertaken in order to achieve the purpose of boarding schools that hadplanned to develop and manage resources and sources of funding and the potentialheld in the boarding school system effectively and efficiently. This activity can bestarted from the planning, organizing, implementing up to scrutiny. In thefinancial management at the school began with budget planning up to monitoringand financial accountability.Financial management of the Islamic boarding school is one of the substancesmanagement of educational institutions which will in turn determine the smoothoperation of the Islamic boarding school. As the case on the substance of educationin general management, financial management activities of the boarding schoolshould be done through the process of planning, organizing, directing,coordinating, monitoring or controlling. Some activities such as financialmanagement and assign an activity to obtain funding sources, utilization of funds,reporting, inspection and accountability.AbstrakAda tiga faktor yang berperan dalam sistem penyelenggaraan PondokPesantren yaitu, manajemen sebagai faktor upaya, organisasi sebagai faktorSarana, dan administrasi sebagai faktor karsa. Ketiga faktor ini memberiarah dan perpaduan dalam merumuskan, mengendalikan,penyelenggaraan, mengawasi serta menilai pelaksanaan kebijakankebijakan dalam usaha menyelenggarakan kegiatan pendidikan yangsesuai dengan tujuan setiap Pondok Pesantren.Salah satu komponen manajemen sebagai upaya dalam pondokpesantren adalah manajemen keuangan. Manajemen keuangan pondokpesantren merupakan kegiatan yang dilakukan guna mencapai tujuanpondok pesantren yang telah direncanakan dengan mengembangkan danmengelola sumber daya dan sumber dana serta potensi-potensi yangdimiliki dalam sistem pondok pesantren secara efektif dan efisien. Kegiatanini dapat dimulai dari perencanaan, pengorganisasian, pelaksanaan sampaidengan pengawasan. Dalam manajemen keuangan di sekolah tersebutdimulai dengan perencanaan anggaran sampai dengan pengawasan danpertanggung jawaban keuangan.Manajemen keuangan pondok pesantren merupakan salah satusubstansi manajamen lembaga pendidikan yang akan turut menentukankelancaran kegiatan pondok pesantren. Seperti halnya yang terjadi padasubstansi manajemen pendidikan pada umumnya, kegiatan manajemenkeuangan pondok pesantren seyogyanya dilakukan melalui prosesperencanaan, pengorganisasian, pengarahan, pengkoordinasian,pengawasan atau pengendalian. Beberapa kegiatan manajemen keuanganberupa kegiatan memperoleh dan menetapkan sumber-sumber pendanaan,pemanfaatan dana, pelaporan, pemeriksaan dan pertanggung jawaban.